Interspecific competition mediated by climate change: Which interaction between brown and mountain hare in the Alps? - Bisi, F.; Wauters, L. A.; Preatoni, D.; Martinoli, A. (Mammalian Biology, 2015)
CO2 levels and consequently temperatures are expected to increase in the next years. Such quick and drastic changes in climate are likely to affect species distribution. According to future climate scenarios some species will have the possibility to colonise new areas, mainly due to expansion of suitable habitat conditions, whereas other species could be negatively affected due to habitat reduction. In this study, we analysed, in the perspective stated above, the distribution of two hare species: the mountain hare (Lepus timidus) and the brown hare (Lepus europaeus), across Central Italian Alps. Mountain hare on the Alps is a relict species, while brown hare is widespread all over Italy and also across the Alps at lower elevations. We applied future climate scenarios to both hare species to understand how climate change could affect their distribution in the next 70 years. Mountain hare distribution surface area is predicted to decrease in the next few years at its southern edge, but the species should expand its range in northern areas. Interestingly, brown hare distribution seems to be unaffected by climate changes, since no evident “area of substitution” appeared in our simulations. Hence, contrary to one’s expectations based on the two species different niches, while we were able to predict a reduction in mountain hare distribution, our simulations did not show a substitution of the mountain hare by the more generalist brown hare at the southern margins of its distribution.